Feasibility of Developing Reed Stems as a Checkerboard Barrier to Stabilize Shifting Sands - Maryam Bagherpour; Salman Zare; Mohammadreza Ekhtesasi; Aliakbar Nazari Samani; Masoumeh Salehi morkani; Ghasem Ghoohestani; Majid Akhshi (مدیریت بیابان)
Extended Abstract IntroductionWind erosion is one of the natural and important factors that contribute to desertification and land degradation in semi-arid, arid, and hyper-arid regions. Wind erosion is more likely to occur in these areas, which encompass 40% of the earth's surface, due to drought and low soil moisture, limited vegetation, soil characteristics, and erosive winds. Sand transport by erosive winds is a common wind process in arid and semi-arid regions, and it has become a widespread global problem. The biological and economic resources are damaged by this process. To control wind erosion and stabilize shifting sands in these areas, a barrier can be used to reduce wind speed to less than the threshold speed of wind erosion. Depending on the purpose, sand barriers can be used in different heights, dimensions, and arrangements. One of these barriers is a straw checkerboard barrier. The use of this method began in the Soviet Union; then it was transferred to China. Ghana, Egypt, and Mongolia have also introduced and used it in a limited capacity. Sand barriers have a long history in Iran, but their use has declined due to limited and scattered applications. Barriers can be constructed in every region using materials like reed plant stems, cotton plant stems, palm tree leaves, and straw. The aim of this research is to evaluate the efficiency of a checkerboard barrier made from the stem of a reed plant in stabilizing shifting sands. Compared to other materials, their use is cheaper and does not cause any environmental pollution in nature. By controlling wind erosion, improving the conditions of the area and reducing damages caused by the shifting sands, it leads to achieving sustainable development. Material and MethodsThe research was conducted in the sand dunes surrounding the village of Hossein Abad Mish Mast in the center of Qom province. The results of the sand rose and wind rose demonstrate that the winds in this region are multidirectional. This research examined the feasibility of utilizing a checkerboard barrier made from reed stems. In order to attain this objective, the surface of a sand dune was covered with the barriers mentioned. The height of these barriers was about 20 cm. The characteristics of sediment grain size were assessed by sampling the surface of the sand inside checkerboard barriers and the control dune in this research. Also, mode, average diameter, skewness, and sorting were investigated.A stabilization efficiency coefficient was calculated to evaluate the impact of the barrier on stabilizing sand dunes. For this purpose, wooden stacks were installed in different parts of the dunes in such a way that they could well express the amount of sand detachment and deposition, and in general the changes in the mobility and displacement of the dunes.The checkerboard barrier's concave shape was measured by installing steel stacks with 10-cm intervals vertically inside a cell on the windward side of the dune. Weekly monitoring of the steel stacks resulted in the drawing of the concave curve of the barrier in Excel.Results and DiscussionThe reed stem barrier's sediment grain size characteristics showed that it had a significant impact on the accumulation of fine sand particles compared to the control. Consequently, the particles are scattered within the diameter layer of 250-125 microns, while the granulation analysis before the barrier and control dune was implemented revealed that approximately 64% of the particles were scattered within the diameter layer of 250-500 microns. The control dune sediment granulation analysis showed that the particles' average diameter increased by 45.5% from the control dune sample before the barrier was implemented. The reason for this is that the activity of erosive winds in the region has increased. The wind flow passes a large amount of sand particles over the dune due to the intensity of wind erosion in the region. Smaller particles are transported and larger particles remain on the surface of the dunes due to the absence of barriers in the way of wind and sand flow.According to the concave shape of the checkerboard barrier, a small amount of sand particles was observed in the examined cell. The concave surface was not formed during the study period. The height and density of the reed stem barrier are the reasons for this. The height of the reed stem barrier, which is 30 cm, and its semi-denseness caused the flow of sand and wind to lose its energy upon hitting the first rows of the barrier, and deposit the sand particles in the first rows. Therefore, there is a lack of particle deposition in the middle grids of the dune. Using reed stem barriers to control wind erosion is one of the appropriate and effective measures that stabilize the surface of sand dunes. In fragile ecological conditions of desert areas, where it is not possible to establish a plant without support, this method is highly effective.